Preclinical Alzheimer's disease and longitudinal driving decline. Issue 1 (23rd December 2016) - Roe, Catherine M.; Babulal, Ganesh M.; Head, Denise M.; Stout, Sarah H.; Vernon, Elizabeth K.; Ghoshal, Nupur; Garland, Brad; Barco, Peggy P.; Williams, Monique M.; Johnson, Ann; Fierberg, Rebecca; Fague, M. Scot; et al.
Abstract: Introduction: Links between preclinical Alzheimer's disease (AD) and driving difficulty onset would support the use of driving performance as an outcome in primary and secondary prevention trials among older adults (OAs). We examined whether AD biomarkers predicted the onset of driving difficulties among OAs. Methods: One hundred four OAs (65+ years) with normal cognition took part in biomarker measurements, a road test, clinical and psychometric batteries, and self‐reported their driving habits. Results: Higher values of cerebrospinal fluid (CSF) tau/Aβ42 and phosphorylated tau (ptau181 )/Aβ42 ratios, but not uptake on Pittsburgh compound B amyloid imaging ( P  = .12), predicted time to a rating of marginal or fail on the driving test using Cox proportional hazards models. Hazards ratios (95% confidence interval) were 5.75 (1.70–19.53), P  = .005 for CSF tau/Aβ42 ; 6.19 (1.75–21.88), and P  = .005 for CSF ptau181 /Aβ42 . Discussion: Preclinical AD predicted time to receiving a marginal or fail rating on an on‐road driving test. Driving performance shows promise as a functional outcome in AD prevention trials.